The efficacy of the eclectic approach on students language performance in ESL/EFL classrooms: an overview (2019 - 2023) - Ab. Ghafar, Nur Maheerah Hanun; Rahmam, Suhailah; Abd Rahman, Siti Fatimah (Human Resource Management Academic Research Society, 2023)
Eclecticism combines various approaches and methods based on learner requirements and classroom circumstances since relying on a single conventional method may not maximise learning outcomes. This study aims to explore the effectiveness of the eclectic approach in improving students' language performance and examine the commonly paired combination of English Language Teaching (ELT) methods. This traditional literature review selected a total of 18 articles. The findings highlight the effectiveness of the eclectic approach in enhancing the learning experience, speaking skills, and communication skills. Besides, Communicative Language Teaching (CLT), Task-based Learning (TBL), Grammar Translation Method (GTM), and Audio-Lingual Method (ALM) were commonly blended in language teaching and learning. This study increases the literature and serves as guidelines for teachers in implementing eclecticism in English as a second language (ESL) or English as a Foreign Language (EFL) contexts. It emphasises the importance of providing adequate training to educators to enhance their pedagogical skills and effectively use the eclectic approach.